M2 macrophage-derived exosomes promote lung adenocarcinoma progression by delivering miR-942. (1st February 2022) - Wei, Ke; Ma, Zijian; Yang, Fengming; Zhao, Xin; Jiang, Wei; Pan, Chunfeng; Li, Zhihua; Pan, Xianglong; He, Zhicheng; Xu, Jing; Wu, Weibing; Xia, Yang; et al.
Abstract: Tumor-associated macrophages (TAMs) are the major components of the tumor microenvironment that contribute to metastasis in lung adenocarcinoma (LUAD). The potential of TAM-derived exosomes for biomarker discovery in tumor initiation and progression has been recently reported. However, studies on macrophage-derived exosomes in LUAD remain limited. We investigated the role of M2 macrophage-derived exosomes in LUAD both in vivo and in vitro and its underlying mechanism. We showed that the infiltration of M2 macrophages was positively correlated with LUAD metastasis. M2 macrophage-derived exosomes could be taken up by LUAD cells to promote cell migration, invasion, and angiogenesis. Furthermore, miR-942 could be packaged into exosomes secreted by M2 macrophages. Mechanistically, exosomal miR-942 regulates FOXO1 protein expression by binding to the 3′-UTR region of FOXO1 and further alleviates β-catenin inhibition in LUAD cells. Collectively, we demonstrated that M2 macrophage-derived miRNA-containing exosomes promote LUAD cell invasion and migration and facilitate angiogenesis, thereby providing a new therapeutic target for metastatic LUAD. Highlights: Metastatic lung adenocarcinoma tissues had high M2 macrophage infiltration. M2 macrophage-derived exosomal miR-942 promoted lung tumor metastasis in vivo. M2 macrophage-derived exosomal miR-942 induced angiogenesis in vivo. miR-942 regulates FOXO1 expression to activate the Wnt/β-catenin pathway.